Understanding Conceptual Climate Change Meanings and Preferences of Multi-Actor Professional Leadership in New York. Issue 3 (26th May 2016) - Keenan, Jesse M.; King, David A.; Willis, Derek
Abstract: This article sets out to evaluate the range of meanings and preferences for the concepts of adaptation, resilience, mitigation and coping of a variety of professionals in New York who are undertaking leadership positions in developing climate change policies and practices. This article positions a normative set of simplified meanings for each of the aforementioned concepts based on a review of existing literature. Utilizing a survey, these normative meanings are evaluated by and between the: (a) concepts and meanings; (b) concepts and applications and (c) applications and preferences, as applied to various risk-based scenarios ranging from sea-level rise to heat waves. This survey tests the hypotheses that the respondents: (i) are unable to consistently match the concept of resiliency with the normative meanings or applications: and (ii) will not consistently show a preference for resilience applications or outcomes ahead of other concepts. The results of the survey confirm both hypotheses, which is demonstrative of the inadequacy of the current framework dominated by a narrowly defined framework for resilience. It is anticipated that the results of this article will advance an argument for the necessity to develop consistent meanings for concepts which bridge the scientific, policy and popular domains.